Casting method for refining alloy phase in hypereutectic aluminum alloy
By adding specific chemical components and grain refining agents during the casting process and using ultrasonic treatment, the alloy phase in the overeutectic aluminum alloy is refined, which solves the problem of coarse alloy phase in traditional casting and improves the mechanical and thermal properties of the material.
Patent Information
- Application Number
- CN202411721185.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-14
AI Technical Summary
The coarse alloy phase formed during traditional casting affects the mechanical properties and processing properties of overeutectic aluminum alloys. The existing refinement methods have problems such as uneven distribution of alloy phases and difficulty in dimensional control.
A casting method for refining the alloy phase in a supereutectic aluminum alloy is adopted. By placing a supereutectic aluminum alloy with specific chemical components, it is melted and stirred, added grain refining agent and refining agent, used ultrasonic treatment, and finally casting to refine the alloy phase.
The uniform refinement of the alloy phase is achieved, the tensile strength, elongation and thermal conductivity of the overeutectic aluminum alloy is improved, the thermal expansion coefficient is reduced, and the overall performance of the material is improved.
Smart Images

Figure BDA0005158073300000081 
Figure BDA0005158073300000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of aluminum alloy casting, and in particular to a casting method for refining alloy phases in hypereutectic aluminum alloys. Background Art
[0002] Due to its excellent properties, hypereutectic aluminum alloys have broad application prospects in aerospace, automobile manufacturing and other fields. However, the coarse alloy phase formed in the traditional casting process seriously affects the mechanical properties and processing properties of this type of material. In order to overcome this problem, researchers have made certain progress by adjusting the chemical composition and heat treatment process to refine the alloy phase. Despite this, existing methods still have problems such as uneven distribution of alloy phases and difficulty in size control, which limits the further improvement of material performance.
[0003] In actual production, common methods for refining alloy phases include adding refiners, pretreatment solutions, and changing heat treatment processes. Among them, adding refiners is one of the most commonly used methods. By adding an appropriate amount of refiners to the molten aluminum alloy, the fine dispersion of the alloy phase can be promoted. However, although the method of adding refiners can refine the alloy phase to a certain extent, there is a problem of uneven dispersion leading to segregation, so it needs to be improved. Summary of the invention
[0004] In order to refine the alloy phase in the hypereutectic aluminum alloy, the present application provides a casting method for refining the alloy phase in the hypereutectic aluminum alloy.
[0005] The present application provides a casting method for refining the alloy phase in a hypereutectic aluminum alloy using the following technical solution: A casting method for refining alloy phases in a hypereutectic aluminum alloy comprises the following steps: (1) preparing a hypereutectic aluminum alloy, wherein the hypereutectic aluminum alloy contains the following components in percentage by weight: 18.5-19% silicon, 4.6-5.2% copper, 0.35-0.45% magnesium, 4.24-4.28% nickel, 0.01-0.05% phosphorus, and the balance being aluminum and unavoidable impurities; (2) melting according to the above nominal composition, heating to 750-800° C., and obtaining a molten aluminum alloy liquid after melting; (3) adding a grain refiner to the molten aluminum alloy liquid, raising the temperature to 770-830° C., stirring to promote uniform distribution of the refiner, and using ultrasonic treatment while stirring to obtain a treated aluminum alloy liquid; (4) preparing a refining solution, adding the refining agent and the refining solution to the treated aluminum alloy liquid, cooling the temperature to 700-730° C., stirring and ultrasonically treating the liquid while adding the refining agent, and passing argon gas to remove impurities to obtain a refined aluminum alloy liquid; (5) Scoop out the oxide scale on the surface of the refined alloy liquid and cast it at 720°C-750°C to obtain a hypereutectic aluminum alloy.
[0006] Silicon can improve the wear resistance and heat resistance of hypereutectic aluminum alloys. The high hardness of the silicon phase can withstand friction loads and maintain stable performance at high temperatures. Copper can improve the strength of the alloy and enhance the mechanical properties of the alloy through mechanisms such as solid solution strengthening. Magnesium can improve the toughness and processing properties of the alloy and participate in the formation of strengthening phases during the solidification process of the alloy. Nickel helps to improve the high-temperature strength and corrosion resistance of the alloy and enhance the stability of the alloy in complex environments. Phosphorus can initially refine the grains and change the solidification structure of the alloy by forming heterogeneous nucleation cores, reducing the formation of coarse grains. Grain refiners provide more heterogeneous nuclei for alloy solidification. core, inhibiting grain growth; subsequently adding refining agent and refining solution, stirring, ultrasonic treatment and argon gas are carried out at the same time to further remove impurities and improve the quality of the alloy; these operations can make the silicon phase distribution more uniform and smaller, reduce the splitting effect of coarse silicon phase on the matrix, and the refined grains and silicon phases increase the grain boundary area, hinder the movement of dislocations, and require greater external force to make dislocations pass through the grain boundaries when the material is subjected to stress. At the same time, grain refinement makes the material deformation more uniform, reduces stress concentration, and reduces the possibility of crack generation and expansion, thereby improving the tensile strength, elongation and thermal conductivity of the hypereutectic aluminum alloy and reducing the thermal expansion coefficient.
[0007] Preferably, the silicon is added in the form of silicon ingots, the copper is added in the form of aluminum-copper master alloy, the magnesium is added in the form of aluminum-magnesium master alloy, the nickel is added in the form of aluminum-nickel master alloy, and the phosphorus is added in the form of aluminum-phosphorus master alloy.
[0008] Copper, magnesium and nickel are added in the form of aluminum-copper, aluminum-magnesium and aluminum-nickel master alloys, respectively. The use of master alloys can make these elements better dissolved and evenly distributed in the aluminum alloy liquid. The elements can be gradually released and evenly diffused in the alloy liquid, reducing local element enrichment or segregation. Phosphorus is added in the form of aluminum-phosphorus master alloy, which is convenient for precise control of the phosphorus content. During the solidification process of the alloy, phosphorus can serve as a heterogeneous nucleation core, increase the number of crystal nuclei, effectively refine the grains, reduce the formation of coarse grains, and cooperate with other elements to optimize the alloy phase organization, thereby improving the tensile strength, elongation and thermal conductivity of the hypereutectic aluminum alloy and reducing the thermal expansion coefficient.
[0009] Preferably, the grain refiner comprises metal-doped mesoporous silica.
[0010] Metal-doped mesoporous silica has a large specific surface area and rich pore structure. In the molten aluminum alloy liquid, it can provide a large number of effective heterogeneous nucleation sites for alloy solidification. These sites can promote the formation of crystal nuclei, so that grains can be generated in large quantities in the early solidification stage, thereby effectively inhibiting the growth of grains and achieving the refinement of the alloy phase. Metal doping can further adjust the properties of mesoporous silica, enable it to better interact with the aluminum alloy liquid, and be more conducive to improving the refinement effect, and ultimately improve the performance of the hypereutectic aluminum alloy.
[0011] Preferably, the raw materials for preparing the metal-doped mesoporous silica include tetraethyl orthosilicate, strontium chloride and ytterbium nitrate.
[0012] Ytterbium, as a rare earth element, can change the growth morphology of the alloy in the alloy liquid. It can be adsorbed on the growing crystal plane, reduce the growth rate of the crystal plane, increase the number of nuclei, and thus refine the grains. Strontium can effectively refine the primary silicon by changing the growth mechanism of the silicon phase, inhibiting the coarsening of the silicon phase, and making the primary silicon crystal smaller and more dispersed. These two elements can produce a synergistic effect by doping mesoporous silica. Mesoporous silica has a high specific surface area and rich mesoporous structure. Ytterbium and strontium elements can be enriched on its surface or in the pores. Mesoporous silica provides more dispersion sites for ytterbium and strontium, making them more evenly distributed in the alloy liquid and enhancing their inhibitory effect on grain growth. Mesoporous silica itself can also serve as a heterogeneous nucleation core, synergistically increasing the number of nuclei with ytterbium and strontium, more effectively refining the grains of the hypereutectic aluminum alloy, and further improving the microstructure and properties of the alloy.
[0013] Preferably, the metal-doped mesoporous silica is prepared by the following steps: Adding tetraethyl orthosilicate to an ethanol aqueous solution, adding hydrochloric acid to obtain a precursor solution; dissolving strontium chloride and ytterbium nitrate in water respectively to obtain a strontium chloride aqueous solution and an ytterbium nitrate aqueous solution; adding the strontium chloride aqueous solution and the ytterbium nitrate aqueous solution to the precursor solution, heating and stirring to react, heating in a water bath and then standing to obtain a gel; filtering and washing the gel with ethanol and water respectively, drying to obtain a solid product, and grinding the solid product to obtain metal-doped mesoporous silica.
[0014] The metal-doped mesoporous silica prepared according to the above steps has a good effect of refining the crystal phase, can effectively improve the tensile strength, elongation and thermal conductivity of the hypereutectic aluminum alloy, and reduce the thermal expansion coefficient.
[0015] Preferably, the grain refiner is added in an amount of 0.5-2% of the molten aluminum alloy.
[0016] Adding grain refiner within the above range can provide an appropriate amount of heterogeneous nucleation cores in the alloy liquid without introducing too many impurities, forming sufficient crystal nuclei and giving full play to the role of grain refinement, thereby improving the tensile strength, elongation and thermal conductivity of the hypereutectic aluminum alloy and reducing the thermal expansion coefficient.
[0017] Preferably, the mass ratio of tetraethyl orthosilicate, strontium chloride and ytterbium nitrate is 1:(0.08-0.22):(0.09-0.26).
[0018] By doping in the above proportion, strontium and ytterbium elements can change the surface properties and crystal structure of mesoporous silica, affecting its ability to serve as a heterogeneous nucleation core, enabling it to provide more effective nucleation sites in the aluminum alloy liquid. The three work synergistically to fully refine the grains of the alloy during solidification, thereby improving the comprehensive performance of the hypereutectic aluminum alloy.
[0019] Preferably, the refining agent includes hexachloroethane, and the refining solution includes potassium fluorotitanate, potassium fluoroborate and cerium nitrate.
[0020] The gas produced by the decomposition of the refining agent hexachloroethane in the aluminum alloy liquid can adsorb and entrain impurities, effectively remove the gas and inclusions in the alloy liquid, purify the melt, and improve the purity of the alloy liquid; potassium fluorotitanate and potassium fluoroborate can decompose titanium, boron and other elements in the aluminum alloy liquid, these elements can serve as heterogeneous nucleation cores, further increase the number of crystal nuclei and refine the grains; the cerium element in cerium nitrate is highly active. During the solidification process of the alloy, cerium can be concentrated at the grain boundary, reduce the interfacial energy, and inhibit grain growth. At the same time, it interacts with other elements to form new compounds to optimize the alloy phase structure, which helps to improve the quality and performance of hypereutectic aluminum alloys and make the alloy structure more uniform and fine.
[0021] Preferably, in step (3), the stirring speed is 100-120 rpm, the ultrasonic frequency is 20-25 kHz, and the power is 2-3 kW.
[0022] Stirring and ultrasonic treatment according to the above parameters can make the added grain refiner fully and evenly dispersed in the molten aluminum alloy liquid, avoid the refiner agglomeration, break the dendrites in the alloy liquid, make the crystal nucleus more dispersed, and promote better mixing of the refiner and the alloy liquid; the two complement each other and can more effectively refine the alloy phase.
[0023] Preferably, in step (4), the stirring speed is 80-100 rpm, the ultrasonic frequency is 20-22 kHz, and the power is 1.5-2 kW.
[0024] Treatment according to the above parameters can promote the effective function of the refining agent to remove impurities and refine the solution, enhance the refinement effect on the alloy phase, and help improve the quality and performance of hypereutectic aluminum alloys.
[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. Silicon can improve the wear resistance and heat resistance of hypereutectic aluminum alloys. The high hardness of the silicon phase can withstand friction loads and maintain stable performance at high temperatures. Copper can improve the strength of the alloy and enhance the mechanical properties of the alloy through solid solution strengthening and other mechanisms. Magnesium can improve the toughness and processing properties of the alloy and participate in the formation of strengthening phases during the solidification process of the alloy. Nickel helps to improve the high-temperature strength and corrosion resistance of the alloy and enhance the stability of the alloy in complex environments. Phosphorus can initially refine the grains and change the solidification structure of the alloy by forming heterogeneous nucleation cores, reducing the formation of coarse grains. Grain refiners provide more heterogeneous nucleation for alloy solidification. The core is refined to inhibit grain growth; refining agent and refining solution are subsequently added, and stirring, ultrasonic treatment and argon gas are carried out at the same time to further remove impurities and improve the quality of the alloy; these operations can make the silicon phase more evenly distributed and smaller in size, reduce the splitting effect of coarse silicon phase on the matrix, and the refined grains and silicon phases increase the grain boundary area, hinder the movement of dislocations, and require greater external force to make dislocations pass through the grain boundaries when the material is subjected to stress. At the same time, grain refinement makes the material deform more evenly, reduces stress concentration, and reduces the possibility of crack generation and expansion, thereby improving the tensile strength, elongation and thermal conductivity of the hypereutectic aluminum alloy and reducing the thermal expansion coefficient.
[0026] 2. As a rare earth element, ytterbium can change the growth morphology of the alloy in the alloy liquid. It can be adsorbed on the growing crystal plane, reduce the growth rate of the crystal plane, increase the number of nuclei, and thus refine the grains. Strontium can effectively refine the primary silicon by changing the growth mechanism of the silicon phase, inhibiting the coarsening of the silicon phase, and making the primary silicon crystal smaller and more dispersed. These two elements doped into mesoporous silica can produce a synergistic effect. Mesoporous silica has a high specific surface area and rich mesoporous structure. Ytterbium and strontium elements can be enriched on its surface or in the pores. Mesoporous silica provides more dispersion sites for ytterbium and strontium, making them more evenly distributed in the alloy liquid, and enhancing its inhibitory effect on grain growth. Mesoporous silica itself can also serve as a heterogeneous nucleation core, synergistically increasing the number of nuclei with ytterbium and strontium, more effectively refining the grains of the hypereutectic aluminum alloy, and further improving the microstructure and properties of the alloy.
[0027] 3. The gas produced by the decomposition of the refining agent hexachloroethane in the aluminum alloy liquid can absorb and entrain impurities, effectively remove the gas and inclusions in the alloy liquid, purify the melt, and improve the purity of the alloy liquid; potassium fluorotitanate and potassium fluoroborate can decompose titanium, boron and other elements in the aluminum alloy liquid. These elements can serve as heterogeneous nucleation cores to further increase the number of crystal nuclei and refine the grains; the cerium element in cerium nitrate has the characteristics of high activity. During the solidification process of the alloy, cerium can be concentrated at the grain boundary, reduce the interfacial energy, and inhibit the growth of grains. At the same time, it interacts with other elements to form new compounds to optimize the alloy phase structure, which helps to improve the quality and performance of hypereutectic aluminum alloys and make the alloy structure more uniform and fine. DETAILED DESCRIPTION
[0028] The present application example discloses a casting method for refining the alloy phase in a hypereutectic aluminum alloy. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the examples: Preparation Example 1 Preparation of Metal-doped Mesoporous Silica Add tetraethyl orthosilicate to an ethanol aqueous solution, add hydrochloric acid so that the mass ratio of tetraethyl orthosilicate, ethanol, water and hydrochloric acid is 1:1:1:0.01, and obtain a precursor solution; dissolve strontium chloride and ytterbium nitrate in water respectively to obtain a strontium chloride aqueous solution and an ytterbium nitrate aqueous solution; add the strontium chloride aqueous solution and the ytterbium nitrate aqueous solution to the precursor solution so that the mass ratio of tetraethyl orthosilicate, strontium chloride and ytterbium nitrate is 1:0.08:0.26, stir and react at 40°C at a speed of 200rpm for 4h, transfer to a 60°C water bath and stand for 8h to obtain a gel; filter and wash the gel with ethanol and deionized water respectively, dry in a vacuum drying oven at 80°C to obtain a solid product, and grind the solid product to obtain metal-doped mesoporous silica.
[0029] Preparation Example 2 Preparation Example 2 is based on Preparation Example 1. The only difference between Preparation Example 2 and Preparation Example 1 is that the mass ratio of tetraethyl orthosilicate, strontium chloride and ytterbium nitrate in Preparation Example 2 is 1:0.22:0.09.
[0030] Preparation Example 3 Preparation Example 3 is based on Preparation Example 1. The only difference between Preparation Example 3 and Preparation Example 1 is that the mass ratio of tetraethyl orthosilicate, strontium chloride and ytterbium nitrate in Preparation Example 3 is 1:0.15:0.175.
[0031] Preparation Example 4 Preparation Example 4 is based on Preparation Example 1. The only difference between Preparation Example 4 and Preparation Example 1 is that the mass ratio of tetraethyl orthosilicate, strontium chloride and ytterbium nitrate in Preparation Example 4 is 1:0.04:0.4.
[0032] Preparation Example 5 Preparation Example 5 is based on Preparation Example 1. The only difference between Preparation Example 5 and Preparation Example 1 is that the mass ratio of tetraethyl orthosilicate, strontium chloride and ytterbium nitrate in Preparation Example 5 is 1:0.35:0.05.
[0033] Preparation Example 6 Preparation Example 6 is based on Preparation Example 1, and the only difference between Preparation Example 6 and Preparation Example 1 is that ytterbium nitrate is not added in Preparation Example 6.
[0034] Example 1 (1) preparing a hypereutectic aluminum alloy, wherein the hypereutectic aluminum alloy contains the following components in percentage by weight: 18.5% silicon, 4.6% copper, 0.35% magnesium, 4.24% nickel, 0.01% phosphorus, and the balance being aluminum and unavoidable impurities; (2) According to the above nominal composition, aluminum-30% copper master alloy, aluminum-35% magnesium master alloy, aluminum-20% nickel master alloy, and aluminum-5% phosphorus master alloy are added into a medium frequency vacuum induction furnace, and finally silicon ingots are added in three times, and the temperature is raised to 750° C. After melting, the temperature is kept for 20 minutes to obtain a molten aluminum alloy liquid; (3) adding 0.5% of the metal-doped mesoporous silica prepared in Preparation Example 1 to the molten aluminum alloy liquid, heating to 770° C., and treating with ultrasound for 15 min while stirring at a stirring speed of 100 rpm, an ultrasound frequency of 20 kHz, and a power of 2 kW to obtain a treated aluminum alloy liquid; (4) preparing a refinement solution, which is an aqueous solution, adding a refining agent and the refining solution to the treated aluminum alloy liquid, cooling the temperature to 700° C., wherein the refining agent accounts for 0.1% of the mass of the treated aluminum alloy liquid, potassium fluorotitanate accounts for 0.1% of the mass of the treated aluminum alloy liquid, potassium fluoroborate accounts for 0.05% of the mass of the treated aluminum alloy liquid, and cerium nitrate accounts for 0.03% of the mass of the treated aluminum alloy liquid; while adding, stirring and ultrasonic treatment are performed for 30 minutes, the stirring speed is 80 rpm, the ultrasonic frequency is 20 kHz, the power is 1.5 kW, argon gas is passed to remove impurities, and the argon gas flow rate is 15 L / min, to obtain a refined aluminum alloy liquid; (5) The oxide scale on the surface of the refined alloy liquid is scooped out and poured at 720°C to obtain a hypereutectic aluminum alloy.
[0035] Example 2 (1) preparing a hypereutectic aluminum alloy, wherein the hypereutectic aluminum alloy contains the following components in percentage by weight: 19% silicon, 5.2% copper, 0.45% magnesium, 4.28% nickel, 0.05% phosphorus, and the balance being aluminum and unavoidable impurities; (2) According to the above nominal composition, aluminum-30% copper master alloy, aluminum-35% magnesium master alloy, aluminum-20% nickel master alloy, and aluminum-5% phosphorus master alloy are added into a medium frequency vacuum induction furnace, and finally silicon ingots are added in three times, and the temperature is raised to 800° C. After melting, the temperature is kept for 15 minutes to obtain a molten aluminum alloy liquid; (3) adding 2% of the metal-doped mesoporous silica prepared in Preparation Example 2 to the molten aluminum alloy liquid, heating to 830° C., and treating with ultrasound for 10 min while stirring at a stirring speed of 120 rpm, an ultrasound frequency of 25 kHz, and a power of 3 kW to obtain a treated aluminum alloy liquid; (4) preparing a refinement solution, which is an aqueous solution, adding a refining agent and the refining solution to the treated aluminum alloy liquid, cooling the temperature to 730° C., wherein the refining agent accounts for 0.2% of the mass of the treated aluminum alloy liquid, potassium fluorotitanate accounts for 0.5% of the mass of the treated aluminum alloy liquid, potassium fluoroborate accounts for 0.3% of the mass of the treated aluminum alloy liquid, and cerium nitrate accounts for 0.2% of the mass of the treated aluminum alloy liquid; while adding, stirring and ultrasonic treatment are performed for 20 minutes, the stirring speed is 100 rpm, the ultrasonic frequency is 22 kHz, the power is 2 kW, argon gas is passed to remove impurities, and the argon gas flow rate is 20 L / min, to obtain a refined aluminum alloy liquid; (5) Scoop out the oxide scale on the surface of the refined alloy liquid and cast it at 750°C to obtain a hypereutectic aluminum alloy.
[0036] Example 3 (1) preparing a hypereutectic aluminum alloy, wherein the hypereutectic aluminum alloy contains the following components in percentage by weight: 18.75% silicon, 4.9% copper, 0.4% magnesium, 4.26% nickel, 0.03% phosphorus, and the balance being aluminum and unavoidable impurities; (2) According to the above nominal composition, aluminum-30% copper master alloy, aluminum-35% magnesium master alloy, aluminum-20% nickel master alloy, and aluminum-5% phosphorus master alloy are added into a medium frequency vacuum induction furnace, and finally silicon ingots are added in three times, and the temperature is raised to 775° C. After melting, the temperature is kept for 17.5 minutes to obtain a molten aluminum alloy liquid; (3) adding 1.25% of the metal-doped mesoporous silica prepared in Preparation Example 3 to the molten aluminum alloy liquid, heating to 800° C., and treating with ultrasound for 12.5 min while stirring, with a stirring speed of 110 rpm, an ultrasound frequency of 22.5 kHz, and a power of 2.5 kW to obtain a treated aluminum alloy liquid; (4) preparing a refinement solution, which is an aqueous solution, adding a refining agent and the refining solution to the treated aluminum alloy liquid, cooling the temperature to 715° C., wherein the refining agent accounts for 0.15% of the mass of the treated aluminum alloy liquid, potassium fluorotitanate accounts for 0.3% of the mass of the treated aluminum alloy liquid, potassium fluoroborate accounts for 0.175% of the mass of the treated aluminum alloy liquid, and cerium nitrate accounts for 0.115% of the mass of the treated aluminum alloy liquid; while adding, stirring and ultrasonic treatment are performed for 25 minutes, the stirring speed is 90 rpm, the ultrasonic frequency is 21 kHz, the power is 1.75 kW, argon gas is passed to remove impurities, and the argon gas flow rate is 17.5 L / min, to obtain a refined aluminum alloy liquid; (5) The oxide scale on the surface of the refined alloy liquid is scooped out and poured at 735°C to obtain a hypereutectic aluminum alloy.
[0037] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the metal-doped mesoporous silica prepared in Preparation Example 3 is replaced by the metal-doped mesoporous silica prepared in Preparation Example 4.
[0038] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the metal-doped mesoporous silica prepared in Preparation Example 3 is replaced by the metal-doped mesoporous silica prepared in Preparation Example 5.
[0039] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, the metal-doped mesoporous silica prepared in Preparation Example 3 is replaced by the metal-doped mesoporous silica prepared in Preparation Example 6.
[0040] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that the amount of grain refiner added in Example 7 accounts for 0.1% of the molten aluminum alloy liquid.
[0041] Example 8 Example 8 is based on Example 3, and the only difference between Example 8 and Example 3 is that the amount of grain refiner added in Example 8 accounts for 2.5% of the molten aluminum alloy liquid.
[0042] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that in Example 9, cerium nitrate is not added to the thinning solution.
[0043] Example 10 Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that potassium fluorotitanate and potassium fluoroborate are not added to the refinement solution in Example 10.
[0044] Embodiment 11 Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that in step (3) of Example 11, the stirring speed is 60 rpm, the ultrasonic frequency is 30 kHz, and the power is 3.5 kW. Example 12 Example 12 is based on Example 3. The only difference between Example 12 and Example 3 is that in step (3) of Example 12, the stirring speed is 150 rpm, the ultrasonic frequency is 15 kHz, and the power is 1.5 kW.
[0045] Example 13 Example 13 is based on Example 3. The only difference between Example 13 and Example 3 is that in step (4) of Example 13, the stirring speed is 50 rpm, the ultrasonic frequency is 25 kHz, and the power is 2.5 kW.
[0046] Embodiment 14 Example 14 is based on Example 3. The only difference between Example 14 and Example 3 is that in step (4) of Example 14, the stirring speed is 150 rpm, the ultrasonic frequency is 18 kHz, and the power is 1 kW.
[0047] Comparative Example 1 Comparative Example 1 is based on Example 3. The only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the grain refiner is replaced by an aluminum-0.04% strontium-0.2% ytterbium alloy ingot.
[0048] Performance testing (1) GB / T16865-2013 Specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products was selected as the standard to test the tensile strength and elongation of the specimens. Three specimens were prepared for each sample, and the average value was taken after measurement. The results are recorded in Table 1.
[0049] (2) Thermal conductivity and thermal expansion coefficient testing: The thermal conductivity of the sample was calculated by the laser flash method, and the change of the sample length with temperature was measured by a laser displacement sensor. The thermal expansion coefficient was calculated. Each sample was tested three times, and the average value was taken after measurement. The results are recorded in Table 1.
[0050] Table 1 Test results of mechanical properties and thermal properties of hypereutectic aluminum alloy As shown in Table 1, the tensile strength of Examples 1-3 is greater than 192 MPa, the elongation is greater than 8.7%, the thermal conductivity is greater than 207 (W / (m·k)), and the thermal expansion coefficient is less than 17.3×10 -6 / ℃, it can be seen that the hypereutectic aluminum alloy prepared in the present application has good mechanical properties, effectively refines the alloy phase, and has high thermal conductivity and low thermal expansion coefficient.
[0051] It can be seen from Table 1 that the only difference between Example 4-6 and Example 3 is that the proportion parameters of metal-doped mesoporous silica are changed in Example 4-6. Compared with Example 3, the tensile strength, elongation and thermal conductivity of Example 4-6 are reduced, and the thermal expansion coefficient is increased; this is because too much or too little metal element doping will affect the performance of mesoporous silica, and thus affect the synergistic effect of the three. Doping that is not within the specified ratio will lead to a decrease in performance and a worse effect of refining the crystal phase; reducing the types of doped metal elements will reduce the synergistic effect. These changes will cause the performance of hypereutectic aluminum alloy to decline.
[0052] As can be seen from Table 1, the only difference between Examples 7 and 8 and Example 3 is that the addition amount of the grain refiner in Example 7 accounts for 0.1% of the molten aluminum alloy liquid, and the addition amount of the grain refiner in Example 8 accounts for 2.5% of the molten aluminum alloy liquid. Compared with Example 3, the tensile strength, elongation and thermal conductivity of Examples 7 and 8 are reduced, and the thermal expansion coefficient is increased; this is because too little grain refiner cannot provide enough heterogeneous nucleation cores, and too much grain refiner will introduce too many impurities, both of which will affect the performance of the alloy, so that the tensile strength, elongation and thermal conductivity of the hypereutectic aluminum alloy are reduced, and the thermal expansion coefficient is increased.
[0053] As can be seen from Table 1, the only difference between Examples 9 and 10 and Example 3 is that the types of components in the refinement solution are reduced in Examples 9 and 10. Compared with Example 3, the tensile strength, elongation and thermal conductivity of Examples 9 and 10 are reduced, and the thermal expansion coefficient is increased. This is because if there is a lack of multi-component synergy, the effect of crystal phase regulation is reduced, and the basic principles of the performance regulation of each component are different. The combination of multiple action mechanisms can more effectively refine the crystal phase, and reducing the components in the refinement solution will destroy this effect, thereby reducing the tensile strength, elongation and thermal conductivity, and increasing the thermal expansion coefficient.
[0054] It can be seen from Table 1 that the only difference between Example 11-14 and Example 3 is that the stirring and ultrasonic parameters are changed in Example 11-14. Compared with Example 3, the tensile strength, elongation and thermal conductivity of Example 11-14 decrease, and the thermal expansion coefficient increases. This is because the specific speed and power of ultrasound and stirring will affect the performance of the aluminum alloy liquid. Low parameters will reduce the dispersibility, and high parameters will introduce too much gas, which will directly affect the composition and stability of the aluminum alloy liquid, thereby reducing the tensile strength, elongation and thermal conductivity, and increasing the thermal expansion coefficient.
[0055] It can be seen from Table 1 that the only difference between Comparative Example 1 and Example 3 is that: Comparative Example 1 replaces the grain refiner with an aluminum-0.04% strontium-0.2% ytterbium alloy ingot. Compared with Example 3, Comparative Example 1 has a decreased tensile strength, elongation and thermal conductivity, and an increased thermal expansion coefficient. This is because compared with metal-doped mesoporous silica with good dispersion, the alloy ingot has poor dispersion, may have a high local concentration, and has a segregation problem, thereby reducing the effect of grain refinement and affecting the performance of the hypereutectic aluminum alloy.
[0056] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A casting method for refining alloy phase in hypereutectic aluminum alloy, characterized in that: The following steps are involved: (1) preparing a hypereutectic aluminum alloy, wherein the hypereutectic aluminum alloy contains the following components in percentage by weight: 18.5-19% silicon, 4.6-5.2% copper, 0.35-0.45% magnesium, 4.24-4.28% nickel, 0.01-0.05% phosphorus, and the balance being aluminum and unavoidable impurities; (2) melting according to the above nominal composition, heating to 750-800°C, and obtaining molten aluminum alloy liquid after melting; (3) adding a grain refiner to the molten aluminum alloy liquid, heating it to 770-830°C, stirring it to promote uniform distribution of the refiner, and using ultrasonic treatment while stirring to obtain a treated aluminum alloy liquid; (4) preparing a refining solution, adding the refining agent and the refining solution to the treated aluminum alloy liquid, cooling the temperature to 700-730° C., stirring and ultrasonically treating the liquid while adding the refining agent, and passing argon gas to remove impurities to obtain a refined aluminum alloy liquid; (5) Scoop out the oxide scale on the surface of the refined alloy liquid and cast it at 720℃-750℃ to obtain a hypereutectic aluminum alloy.
2. The casting method for refining alloy phase in hypereutectic aluminum alloy according to claim 1, characterized in that: The silicon is added in the form of silicon ingots, the copper is added in the form of aluminum-copper master alloy, the magnesium is added in the form of aluminum-magnesium master alloy, the nickel is added in the form of aluminum-nickel master alloy, and the phosphorus is added in the form of aluminum-phosphorus master alloy.
3. The casting method for refining alloy phase in hypereutectic aluminum alloy according to claim 1, characterized in that: The grain refiner includes metal-doped mesoporous silica.
4. The casting method for refining alloy phase in hypereutectic aluminum alloy according to claim 3, characterized in that: The raw materials for preparing the metal-doped mesoporous silica include tetraethyl orthosilicate, strontium chloride and ytterbium nitrate.
5. The casting method for refining alloy phase in hypereutectic aluminum alloy according to claim 4, characterized in that: The metal-doped mesoporous silica is prepared by the following steps: Adding tetraethyl orthosilicate to an ethanol aqueous solution, adding hydrochloric acid to obtain a precursor solution; dissolving strontium chloride and ytterbium nitrate in water respectively to obtain a strontium chloride aqueous solution and an ytterbium nitrate aqueous solution; adding the strontium chloride aqueous solution and the ytterbium nitrate aqueous solution to the precursor solution, heating and stirring to react, heating in a water bath and then standing to obtain a gel; filtering and washing the gel with ethanol and water respectively, drying to obtain a solid product, and grinding the solid product to obtain metal-doped mesoporous silica.
6. The casting method for refining alloy phase in hypereutectic aluminum alloy according to claim 5, characterized in that: The mass ratio of tetraethyl orthosilicate, strontium chloride and ytterbium nitrate is 1:(0.08-0.22):(0.09-0.26).
7. A casting method for refining alloy phase in hypereutectic aluminum alloy according to claim 6, characterized in that: The grain refiner is added in an amount of 0.5-2% of the molten aluminum alloy liquid.
8. The casting method for refining alloy phase in hypereutectic aluminum alloy according to claim 1, characterized in that: The refining agent includes hexachloroethane, and the refining solution includes potassium fluorotitanate, potassium fluoroborate and cerium nitrate.
9. The casting method for refining alloy phase in hypereutectic aluminum alloy according to claim 1, characterized in that: In the step (3), the stirring speed is 100-120 rpm, the ultrasonic frequency is 20-25 kHz, and the power is 2-3 kW.
10. The casting method for refining alloy phase in hypereutectic aluminum alloy according to claim 1, characterized in that: In step (4), the stirring speed is 80-100 rpm, the ultrasonic frequency is 20-22 kHz, and the power is 1.5-2 kW.